Pengaruh Linguistik Bahasa Ibu dalam Proses Pembelajaran Bahasa Target - M. Dzikrul Hakim Al Ghozali (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2018)
In the process of acquisition of B1, a person has undergone a course (acquisition of language naturally), so automatically all elements of language in B1 will be attached and easily he mastered. Another case with B2, one still has to try (consciously) to master all elements of language about B2. There are several relationships between B1 and B2 that a person is studying, including both language equations and language differences, as well as language structure. The existence of ease in learning B2 because there are some similarities between B1 and B2. Conversely, difficulties arise in learning B2 because of the differences between the two languages, which can even lead to errors. So with this please note that the influence of B1 to B2 and will always exist